Respuesta :

Answer: f(x) = 4*cos(x*2*pi/3)

Where I assumed that the period is 3, instead of 3x

Step-by-step explanation:

In a general equation like:

f(x) = a*cos(b*x)

a is the amplitude.

b is the angular frequency, which is equal to two pi times the inverse of the period.

In this case, we know that the amplitude is 4, then a = 4.

And the period is 3x (i guess that this is wrong because the period should not depend on the variable, as we will see later), then the frequency is:

b = 2*pi/3x

Replacing these in the equation we get:

f(x) = 4*cos(x*2*pi/3x) = 4*cos(2*pi/3)

Then we have no longer a dependence on x.

If the period is equal to 3, then the frequency will be:

b = 2*pi/3

Then the equation now is

f(x) = 4*cos(x*2*pi/3)

This is a cosine function, as we wanted.

ACCESS MORE